Upaya pencegahan pencemaran lingkungan hidup perspektif Undang-Undang No. 32 tahun 2009 tentang perlindungan dan pengelolaan lingkungan hidup - Baihaqi, Imam (Maliki Interdisciplinary Journal, 2024)
In this article, we try to answer the problem, namely how to prevent environmental pollution from the perspective of Law no. 32 of 2009 concerning Environmental Protection and Management What sanctions are given to perpetrators of environmental pollution and destruction. This research uses a form of normative legal research, namely research based on written laws and regulations and various literature related to the issues that will be discussed in this study. By using primary and secondary legal material sources. The results of the research show that legal substances or laws and regulations concerning the environment are the legal basis in the implementation and enforcement of law by law enforcement officials and officials in the context of overcoming environmental problems in Indonesia. Environmental Law Enforcement is closely related to the ability of the apparatus and the compliance of citizens with applicable regulations, which cover three areas of law, namely administrative, criminal and civil. Law enforcement in the licensing sector tends more towards administrative regulations and administrative sanctions. Environmental permits in Indonesia related to environmental issues have been regulated in various types of legislation, in UUPPLH it is explained that licensing functions as an instrument for preventing environmental pollution, as well as preventing environmental damage. Furthermore, every company and/or activity that has an impact on the environment is required to have an AMDAL; UPL UKL; or SPPL.